Exploring the antibacterial mechanism of essential oils by membrane permeability, apoptosis and biofilm formation combination with proteomics analysis against methicillin-resistant staphylococcus aureus - Cailin Tang; Jiali Chen; Lixia Zhang; Rongfei Zhang; Sichen Zhang; Shaoxia Ye; Zhimin Zhao; Depo Yang (Elsevier, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the important causes of food poisoning and infectious diseases worldwide, it can produce a large number of virulence factors, enhance the colonization ability of the host so that it can quickly colonize and spread on the surface of the objects. Essential oil (EO) is one of the natural products with antimicrobial properties, can be used as an important source of antibacterial agent discovery, and has a broad development prospect. However, the unclear mechanisms of antibacterial action have become an obstacle to its further development and use. Hence, the objective of the present study was to reveal the antibacterial mechanism of EO from Amomum villosum Lour (A villosum Lour) against MRSA using label-free quantitative proteomics, investigate the effect of EO on the bacterial proteome, enzymatic activities and leakage of bacterial intracellular biomacromolecule. Proteomic analysis of MRSA in the presence of EO found that a total of 144 differential expressed proteins (DEPs) between the control and treatment group, in which 42 proteins were distinctly up-regulated and 102 proteins were down-regulated. Besides, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis, determination of cell membrane permeability and apoptosis, scanning electron microscopy (SEM) observations, bacterial surface hydrophobicity, and biofilm formation measurement were performed. Collectively, the above results indicated that the cell membrane damage by EO leads to the loss of membrane integrity and causes leakage of intracellular macromolecular substances, inhibition of protein, and biofilm synthesis. These findings manifested that EO exerts antibacterial effect by multiple avenues and expands our understanding of the antibacterial mechanism, it has potential application value in food preservative and pharmaceutical industries.